1990
DOI: 10.1002/ssu.2980060505
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of non‐small cell lung cancer by stage

Abstract: Resection is the treatment of choice for stage I and II non-small cell lung carcinoma. The 5-year survival following resection is 72% in stage I carcinoma and 49% in stage II carcinoma. Resection alone or combined with radiation and/or chemotherapy is also indicated in some patients with stage IIIa disease. The 5 year survival with resection is 56% in tumors invading chest wall (T3N0), 30% in superior sulcus tumors, 30% in patients with N2M0 disease, and 36% in patients with tumors in proximity to carina. Surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…The standards defining this indicator are very well documented [15,16], but interpretation of results is likewise difficult. It is a typical outcome indicator, where the results are influenced by multiple factors.…”
Section: Discussionmentioning
confidence: 98%
“…The standards defining this indicator are very well documented [15,16], but interpretation of results is likewise difficult. It is a typical outcome indicator, where the results are influenced by multiple factors.…”
Section: Discussionmentioning
confidence: 98%
“…2 However, it remains unelucidated whether or not there is any difference in survival after resection between patients who have a small amount of malignant pleural effusion and those who have positive lavage cytology. The standard treatment is still considered to be a surgical resection of the primary tumor in the latter patients.…”
Section: Discussionmentioning
confidence: 99%
“…At present, tumor resection is generally thought to be contraindicated. 2 In the present study, we retrospectively analyzed the above issue by conducting a questionnaire survey through the Japan Clinical Oncology Group (JCOG).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that radiotherapy at a total dose of 54 -64 Gy can eradicate microscopic residual cancer. [25][26][27][28][29][30][31][32] Furthemore, a nonrandomized study of patients with resected N2 cancer 35 indicates a survival advantage for the group of 88 patients who received postoperative radiotherapy. Ten randomized trials [5][6][7][8][9][10][11][12][13][14][15] involving a total of 1711 evaluable patients failed to demonstrate an improve- 11 Lung Cancer Study Group, 10 and the Van Houtte trial 9 ) used doses of 40 Gy, 50 Gy, and 60 Gy, respectively.…”
Section: Discussionmentioning
confidence: 99%